2005
DOI: 10.1063/1.1880437
|View full text |Cite
|
Sign up to set email alerts
|

Emissivity — a remote sensor of giant magnetoresistance

Abstract: A new experimental design for noncontact giant magnetoresistance measurements using the magnetorefractive effect Rev.The link between emissivity in the mid-to-far-infrared regime and electrical conductivity is used to probe magnetoresistance. A direct relationship between the change in radiated flux and giant magnetoresistance is confirmed by experiment. The potential for spatially resolved measurements is also considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…The potential of the MRE to study magnetic thin films has previously been demonstrated. Following its first discovery using Ni 80 Fe 20 /Cu/Co/Cu multilayers in transmission experiments [1], infrared-wavelength MRE measurements have been extended to the reflection geometry [4,5], contributions to the effect from interband transitions [6] and phonon modes have been identified [7], and MRE results compared to magnetic-linear-dichroism and emissivity studies [8,9]. The wide applicability has been demonstrated in studies of the transport properties of GMR granular [5,10], multilayer [11], spin-valve [8,12] thin films, LaSrMnO perovskites [13] and granular metal-insulator systems [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The potential of the MRE to study magnetic thin films has previously been demonstrated. Following its first discovery using Ni 80 Fe 20 /Cu/Co/Cu multilayers in transmission experiments [1], infrared-wavelength MRE measurements have been extended to the reflection geometry [4,5], contributions to the effect from interband transitions [6] and phonon modes have been identified [7], and MRE results compared to magnetic-linear-dichroism and emissivity studies [8,9]. The wide applicability has been demonstrated in studies of the transport properties of GMR granular [5,10], multilayer [11], spin-valve [8,12] thin films, LaSrMnO perovskites [13] and granular metal-insulator systems [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Thus emissivity is expected to increase with the increase of hydrogen in a material. The link between emissivity in the midto-far-infrared regime and electrical conductivity was previously exploited to probe magnetoresistance [37]; a direct relationship between the change in radiated flux and giant magnetoresistance was confirmed experimentally.…”
Section: Link Between Ir Emissivity Intensity and Hydrogenationmentioning
confidence: 93%
“…More recently, emissivity has been demonstrated experimentally as an alternative remote sensor of GMR which offers a more direct and sensitive probe of magnetotransport [6]; infact, a change in emissivity is predicted to be directly proportional to GMR. Emissivity is an emission characteristic of a material defined as the efficiency with which a material radiates energy compared to that of a perfectly radiating black body at the same temperature.…”
Section: Introductionmentioning
confidence: 98%
“…Also, no consideration has yet been made of the thin-film nature of the magnetic materials being investigated, and this is addressed here by adapting a thin-film model of emissivity by Pigeat et al [10]. It is used to directly model the link between emissivity and GMR as a function of film thickness at far IR wavelengths, and is compared to the bulk-material results used in previous studies [6][7][8][9]. The spectral dependence of the emissivity effect at mid-to-far IR wavelengths is also examined using a Drude-type model of refractive index combined with the thin-film emissivity model, and an analytic interpretation at far IR wavelengths is presented.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation